High-Impact Chronic Pain Transition in Lumbar Surgery Recipients. Issue 3 (6th October 2022) - Cook, Chad E; George, Steven Z; Lentz, Trevor; Park, Christine; Shaffrey, Christopher I; Goodwin, C Rory; Than, Khoi D; Gottfried, Oren N
Abstract: Objective: High-impact chronic pain (HICP) is a term that characterizes the presence of a severe and troubling pain-related condition. To date, the prevalence of HICP in lumbar spine surgery recipients and their HICP transitions from before to after surgery are unexplored. The purpose was to define HICP prevalence, transition types, and outcomes in lumbar spine surgery recipients and to identify predictors of HICP outcomes. Methods: In total, 43, 536 lumbar surgery recipients were evaluated for HICP transition. Lumbar spine surgery recipients were categorized as having HICP preoperatively and at 3 months after surgery if they exhibited chronic and severe pain and at least one major activity limitation. Four HICP transition groups (Stable Low Pain, Transition from HICP, Transition to HICP, and Stable High Pain) were categorized and evaluated for outcomes. Multivariate multinomial modeling was used to predict HICP transition categorization. Results: In this sample, 15.1% of individuals exhibited HICP preoperatively; this value declined to 5.1% at 3 months after surgery. Those with HICP at baseline and 3 months had more comorbidities and worse overall outcomes. Biological, psychological, and social factors predicted HICP transition or Stable High Pain; some of the strongest involved social factors of 2 or more to transition to HICP (OR = 1.43; 95% CI = 1.21–1.68), and baseline report of pain/disability (OR = 3.84; 95% CI = 3.20–4.61) and psychological comorbidity (OR = 1.78; 95% CI = 1.48–2.12) to Stable Stable High Pain. Conclusion: The percentage of individuals with HICP preoperatively (15.1%) was low, which further diminished over a 3-month period (5.1%). Postoperative HICP groups had higher levels of comorbidities and worse baseline outcomes scores. Transition to and maintenance of HICP status was predicted by biological, psychological, and social factors.